2023
DOI: 10.1007/s13143-022-00308-y
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally persistent Eurasian cold events and their stratospheric link

Abstract: Persistent boreal winter cold spells (PCEs) can heavily strain the economy and significantly impact everyday life. While sudden stratospheric warmings are considered a precursor for Eurasian (EUR) cold events, these temperature extremes may occur during the full range of stratospheric variability. We investigate PCEs relative to the prevailing stratospheric polar vortex regime before their onset, with a particular focus on extremely weak (SSW) and strong (SPV) stratospheric winds by performing (lagged) composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…On the other hand, when the forecasts are initialized during strong polar vortex conditions, most of the models predict low probabilities (<0.2) of cold events over the study region (Figure 9f,h), which aligns with the expectation that a strong polar vortex is followed by warm anomalies (e.g., Tripathi et al, 2015). Finke et al (2023) suggested that cold Eurasian events following strong polar vortex may be related to downward wave reflection conditions. In this scenario, we considered 140 forecasts for ECMWF, 97 for UKMO, 127 for BoM, 104 for CNRM and 53 for JMA.…”
Section: Reliabilitysupporting
confidence: 74%
“…On the other hand, when the forecasts are initialized during strong polar vortex conditions, most of the models predict low probabilities (<0.2) of cold events over the study region (Figure 9f,h), which aligns with the expectation that a strong polar vortex is followed by warm anomalies (e.g., Tripathi et al, 2015). Finke et al (2023) suggested that cold Eurasian events following strong polar vortex may be related to downward wave reflection conditions. In this scenario, we considered 140 forecasts for ECMWF, 97 for UKMO, 127 for BoM, 104 for CNRM and 53 for JMA.…”
Section: Reliabilitysupporting
confidence: 74%
“…However, most of the results provided in this study are from a zonally‐integrated perspective, and we have not discussed the local and zonally asymmetric downward impacts from the stratosphere on the troposphere, which are more closely related to SSW events of displacement and split types (e.g., Charlton & Polvani, 2007; Lehtonen & Karpechko, 2016; Mitchell et al., 2013). In that case, waves would play an important role (Cohen et al., 2021; Davis et al., 2022; Finke et al., 2023; Gong et al., 2019; Kretschmer et al., 2018; Messori et al., 2022; Perlwitz & Harnik, 2004; Rupp et al., 2022; Shen et al., 2023). Future studies on the relationship between regional cold air transports and the related continental CAOs and the SSW type are needed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Note that our concern here is the zonally integral meridional mass transport across the polar circle. The wave‐contributed weakening of the equatorward cold airmass transport after the anomalous WB‐ST and that during and after negative NAM events may not necessarily represent the local downward wave reflection processes that are known to be favorable for the CAOs occurring in North America (Cohen et al., 2021; Davis et al., 2022; Finke et al., 2023; Gong et al., 2019; Kretschmer et al., 2018; Messori et al., 2022; Rupp et al., 2022; Shen et al., 2023).…”
Section: Stratospheric Downward Impacts Exist Mainly/barely At the Mo...mentioning
confidence: 99%
“…The anomalous flow associated with these opposite, extreme stratospheric states can affect the tropospheric circulation and surface weather (Baldwin and Dunkerton, 2001;Hinssen et al, 2011;Kodera et al, 2013;Davini et al, 2014;Afargan-Gerstman et al, 2020;Domeisen et al, 2020c;White et al, 2020). Previous research has particularly focused on SSW events because of their linkage to extreme weather events (e.g., Domeisen and Butler, 2020;Finke et al, 2023) and periods of higher than usual extended-range and seasonal predictability (e.g., Domeisen et al, 2020b;Zhang et al, 2022), while SPVs have received comparatively less attention, although these events have also been linked to increased surface predictability (Tripathi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%